MAKNA SATYA WAKYA DALAM KAKAWIN KARÓN?NTAKA - Suprapta Pratama, Putu Ari (Humanis, 2013)
Kakawin Karón?ntaka has uniques things that can be seen from the title itself. The titles of this literature is “Karón?ntaka” by “Sang Kawi”(writers) which literally means “the death of Karna”. Generally, the characteristics of the main character is cruel and egoistic. He defends Korawa who likes doing cheating and wickedness. He also opposes the kindness and the rightness. But in this Kakawin Karón?ntaka, the main character “Karna” is become protagonist. That is why the writer is interested in analysing this Kakawin Karón?ntaka in semiotics. In this research is mainly purposed to analyze the meaning of Kakawin Karón?ntaka by matrix and model. The method that is used in collecting data is reading text method. The data were analyzed based on the principle and semiotics as the main base. This research provided the meaning of Kakawin Karón?ntaka and was firstly done by matrix analysis. The matrix of Kakawin Karón?ntaka is “satya wakya”. There is also another meaning of Kakawin Karón?ntaka, that is, loyal to the words (satya wakya).
Keywords: kakawin, matrix, satya wakya.